ANALISIS PROFIL KONSISTENSI REPRESENTASI DAN KONSISTENSI ILMIAH KONSEP FISIKA PADA TOPIK USAHA DAN ENERGI SISWA SMA NEGERI PASCA PEMBELAJARAN JARAK JAUH DI KABUPATEN BANDUNG - Wawan Ruswandi, - (2022)
Information about the profile of representational consistency and scientific consistency is important to know because both of these capabilities related to understanding the concept and the student's ability to use multiple representations. This study aims to analyze the consistency of representation and science high school students in the mastery of physics concepts regarding work and energy during distance learning in the Bandung Regency. The method used is a survey method with a test for the students after implementation of the learning process. The sample size is determined based on the formula Isaac and Michael with the entire student class X population of high schools in Bandung regency. The sampling technique was stratified random sampling. The 19 schools were categorized into upper, middle, and lower cluster schools based on the order in which the results of the Student National Examination were obtained. Data were collected in three schools, which each represent the upper cluster, middle cluster, and lower cluster. The instrument used consisted of eight themes which in each theme there are three questions isomorphic (same context and content) with different representations referring to Representational Variant of Force Concept Inventory (R-FCI). From 450 total research sample size, it found that 17,33% of students are consistent for representational consistency category, 38,45% are moderately consistent, and 44,22% are inconsistent. As for the scientific consistency, it found that 12,44% % of students are consistent, 28,45% are moderately consistent, and 59,11% are inconsistent. These results indicate that students have the ability to use multiple representations, most students are not scientifically consistent with the concepts of work and energy.